Eckehard Schulz's Modern Arabic Book Evaluation According To The Rusydi Ahmad Thu'aimah Concept - Primasti Nur Yusrin Hidayanti; Mirwan Akhmad Taufiq (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2023)
Textbooks are the main component used in assisting educators in delivering learning materials. The selection of the right textbook can affect the achievement of existing learning objectives. The Modern Arabic Book by Eckehard Schulz is a source of learning media in the form of printed books used by students at Sunan Ampel University Surabaya in learning and recognizing Arabic. The purpose of this research is to analyze and assess the suitability of the teaching materials presented in Arabic books with the theoretical principles of textbook development that Rusydi Ahmad Thu'aimah has established. In this study, the researcher used a qualitative descriptive type, and data collection was in document analysis. The study results stated that Eckehard Schulz's Modern Arabic book followed Rusydi Ahmad Thu'aimah's theory in the principle of textbook feasibility. Modern Arabic books contain five main principles in teaching materials, namely valid, meaningful, inclination and attention, worthy of study and global. The presentation of complete teaching materials includes four language skills: speaking, listening, reading and writing. The material is arranged sequentially to make it easier for students. However, some things could be improved in the book, namely, in grouping the main themes in Arabic textbooks.